ANTI-CRISIS MANAGEMENT IN THE FINANCIAL ACTIVITY OF THE BANK: THEORETICAL-METHODOLOGICAL ASPECTS - Пшик , Богдан (Socio-economic relations in the digital society, 2019)
The article analyzes the essence of crisis management in the fi nancial activities of banks. Crisis management of banks should be considered from the standpoint of the development of appropriate strategies within which uses a number of tools and measures to identify, prevent and neutralize the crisis in order to achieve strategic objectives banking. From the point of view of forming the mechanism of crisis management of financial activities of banks, the main principles of it are specified: complexity, functionality; Transparency; controllability; optimality; efficiency; preventive. The sequence of forming the mechanism of crisis management of fi nancial activity of banks is proposed: the definition of clear strategic guidelines in the process of ensuring the development of the bank; defi nition of the goals of crisis management; formulation of the principles of crisis management of the fi nancial activities of the bank; development of a model, methods and procedures that provide maximum eff ect in the implementation of the strategy of crisis management and crisis management measures. High probability of occurrence of crisis phenomena in the process of banks activity necessitates the introduction of specialized measures to counteract their development and neutralization. Systematize the instruments of crisis management in the financial activities of banks (financial, organizational, managerial, information-analytical and legal) in the context of state level and the level of commercial banks aimed at early detection and resolution of problems to prevent the crisis.